2005
DOI: 10.3171/ped.2005.103.4.0353
|View full text |Cite
|
Sign up to set email alerts
|

Genetic considerations in nonsyndromic midline craniosynostoses: a study of twins and their families

Abstract: A midline craniosynostosis is more likely to develop in twins compared with singletons. A genetic component is supported by the higher risk in MZ twins. The presence of an environmental component is reinforced by the high rate of twinning, the normal MZ/DZ ratio, and a less than 100% concordance rate in MZ twins.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 25 publications
1
47
1
Order By: Relevance
“…Varying abnormalities of chromosomes 3q, 7p, 10p, 11q, 15q, and 22q have also been reported [Kini et al, 2010]. Other causal factors are prenatal exposure to valproate [Lajeunie et al, 2001;Kini et al, 2010], fetal or neonatal hyperthyroidism [Azimi et al, 2003], rickets [Lajeunie et al, 1998], multiple pregnancies [Lajeunie et al, 2005], and intrauterine head compression [Hunenko et al, 2001]. The hypothesis of multifactorial inheritance is also supported by a low recurrence rate of 3.2% [Jehee et al, 2005].…”
Section: Discussionmentioning
confidence: 62%
“…Varying abnormalities of chromosomes 3q, 7p, 10p, 11q, 15q, and 22q have also been reported [Kini et al, 2010]. Other causal factors are prenatal exposure to valproate [Lajeunie et al, 2001;Kini et al, 2010], fetal or neonatal hyperthyroidism [Azimi et al, 2003], rickets [Lajeunie et al, 1998], multiple pregnancies [Lajeunie et al, 2005], and intrauterine head compression [Hunenko et al, 2001]. The hypothesis of multifactorial inheritance is also supported by a low recurrence rate of 3.2% [Jehee et al, 2005].…”
Section: Discussionmentioning
confidence: 62%
“…The relationship between paternal age and occurrence of craniosynostosis has not been shown [15]. Most of the previous studies have reported craniosynostosis, especially sagittal and metopic synostosis, to occur more often among boys [19,20,21,22,23]. Some studies found a relationship between the risk of craniosynostosis and the use of infertility treatment such as clomiphene citrate [1,24].…”
Section: Introductionmentioning
confidence: 99%
“…Research to understand the genetic and environmental basis for CS development found higher risk in twins, in males, in infants with birth weight greater than 4 kg, and in births with a maternal age of 35 years and older [1,3,10]. If only one suture is affected, excessive growth will occur in the direction of the closed suture with subsequent skull deformity and cosmetic problems.…”
Section: Discussionmentioning
confidence: 95%